MODEL PEMBUATAN LEMBAR KERJA SISWA BERBASIS PLUGIN WORDPRESS GUNA PENINGKATAN MUTU BAHAN AJAR SISWA SMA (Information Technology and Telematics, 2013)
In the learning process, teachers hoped that the creation of an enabling process interactions between students and teachers, with the communication process. But in reality, the communication process is not always run smoothly. Even the process of communication can cause misunderstandings or misconceptions. Therefore, teachers want to know how active students in the learning process at home is to assign tasks in the Student Worksheet (LKS) as a training tool for students at home. However, students often forget to do the tasks assigned by the teacher with a variety of reasons, one of which is sure to do it. Making interactive worksheets is a solution for students when students feel bored or forget in doing worksheets. Interactive worksheets are worksheets that interact visually, for example, plugin-based interactive worksheets that can be integrated in wordpress. In this study, the model was built based interactive worksheets wordpress plugin. Using MySql database and PHP programming language. By using the wordpress plugin create interactive worksheets that are easy teachers or teams Congress Subject Teacher (MGMPs) to create multiple choice questions and essays that can be done directly by the students. So the teacher or team MGMPs do not need to create worksheets with waiting results are printed. Keywords: LKS, Interactive LKS, Wordpress Plugins, Questions